AH-38 Lectin Histochemistry of the Parotid and Mandibular Glands of Barking Deer, Muntiacus muntjak - I Ketut Mudite Adnyane; Md Zuki Abu Bakar; Noordin Mohamed Mustapha; Srihadi Agungpriyono (Media Veteriner, 2015)
Lectin Histochemistry of the Parotid and Mandibular Glands of Barking Deer, Muntiacus muntjak